Sistema Único de Saúde: garantia e acesso aos direitos de crianças e adolescentes com deficiência no município de São Sebastião - Aragão, Ana Paula Almeida de [UNIFESP] (2018)
This Research Poses Reflections About The Care Network For The Disabled Within Sus (Brazilian Public Health Care System) And The Correlation Between The Health Service Performance With The Assurance Of The Disabled Children And Teenager"S Rights Living In The District Of Maresias, A Municipality Of São Sebastião, São Paulo, Brazil. The Aim Of The Study Was To Analyze The Care Network, To Understand How To Access The Services That Comprise It, And To Investigate How To Ensure The Rights Of Children And Teenagers With Disabilities In São Sebastião Through This Health Attention Network. It Describes The Conceptual Development Of Deficiency Throughout History, Marking The Advance In The Way Of Treating These Subjects. It Demonstrates The Policies Achieved Historically At A National Level, Referencing The Historical Processes Of Several Countries And International Legal Frameworks That Have Influenced The Way In Which Brazil Treats Its Population. It Also Describes The Present-Day Advances, The Sorts Of Struggles